Iskusstvo kino digital archive.
The Iskusstvo Kino Digital Archive captures the complete run (1931-2012) of this esteemed monthly publication in a complete online archive, in full-image and fully searchable text. With more movie screens than any nation at any time, the Soviet Union's cinematic legacy helped shape the artistic and social agenda of the socialist world for most of the twentieth century. Iskusstvo kino, founded in 1931, chronicled that cinematic legacy with its devotion to art in Russian film. Renowned as one of Russia's premier journals of cinema, Iskusstvo kino offers more than Russian and foreign movie reviews, articles on filmmaking and cinema culture, criticism, and essays. Iskusstvo kino traces Russian arts and culture from the 'socialist realism' era -- when film became the prime propaganda tool ("agitki") for instilling Communist fervor in the masses -- all the way through contemporary filmmaking. A monthly publication from 1931-1941, Iskusstvo kino went on hiatus during World War II and then was published irregularly during 1945-1947 and bimonthly during 1947-1951 before resuming monthly publication in 1952.